2019
DOI: 10.1186/s13019-019-0997-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive aortic valve replacement: associations of radiological assessments with procedure complexity

Abstract: Objectives: Limited aortic annulus exposure during minimal invasive aortic valve replacement (mini-AVR) proves to be challenging and contributes to procedure complexity, resulting in longer procedure times. New innovations like sutureless valves have been introduced to reduce procedure complexity. Additionally, preoperative imaging could also contribute to reducing procedure times. Therefore, we hypothesize that Computed Tomography (CT)-image based measurements are associated with mini-AVR complexity. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In 2018, Elattar et al, in their single-centre retrospective study, found that the access angle is strongly associated with procedure complexity; indeed, an access angle of 38 • was a good cut-off to distinguish simple from complex minimally invasive aortic valve replacement [10]; furthermore, in their work, a different kind of angle was considered: Elattar et al considered the angle between the aorta and the surgical access plane, while, in our cohort, we considered the inclination of the aortic annulus on the horizontal plane. On the contrary, Boti et al, in 2019, found that the access angle was not associated with procedure complexity [13].In other recent studies focused on the topic, Jug et al, in 2021, analysed similar anatomical features in the context of anterior mini-thoracotomy or upper mini-sternotomy [14], but they used only rapid-deployment valve prostheses. It is interesting that in their cohort they found that smaller aortic annulus was associated with longer operative times; this difference is probably due to a longer time spent in positioning the sutures with the standard technique in the larger annulus (as in our cohort).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Elattar et al, in their single-centre retrospective study, found that the access angle is strongly associated with procedure complexity; indeed, an access angle of 38 • was a good cut-off to distinguish simple from complex minimally invasive aortic valve replacement [10]; furthermore, in their work, a different kind of angle was considered: Elattar et al considered the angle between the aorta and the surgical access plane, while, in our cohort, we considered the inclination of the aortic annulus on the horizontal plane. On the contrary, Boti et al, in 2019, found that the access angle was not associated with procedure complexity [13].In other recent studies focused on the topic, Jug et al, in 2021, analysed similar anatomical features in the context of anterior mini-thoracotomy or upper mini-sternotomy [14], but they used only rapid-deployment valve prostheses. It is interesting that in their cohort they found that smaller aortic annulus was associated with longer operative times; this difference is probably due to a longer time spent in positioning the sutures with the standard technique in the larger annulus (as in our cohort).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, contrary to prior research, the access angle was not associated with the procedure’s complexity. [ 17 ] 2019 Fluoroscopy This article utilized thermoluminescent dosimeters to measure the radiation exposure across various body regions for patients and operating room medical staff. These findings represent an initial comprehensive comparison of the real-life radiation exposure among operating room personnel and patients when comparing navigation and fluoroscopy usage.…”
Section: Table A1mentioning
confidence: 99%
“…Interestingly, contrary to prior research, the access angle was not associated with the procedure's complexity. [17] 2019 Fluoroscopy…”
Section: Tee and Aimentioning
confidence: 99%
See 1 more Smart Citation
“…The outer contour of the heart is formed by the pericardium and a strip of epicardial fat. The pericardium attaches to large vessels at the level of the aortic arch, forming a kind of "bag", the contents of which are the heart, adipose tissue and parts of large vessels emanating from the heart or flowing into it (15). To determine optimal surgical access, the most important is to obtain dynamic computed tomography angiography images at70% of the cardiac cycle (middiastole) because in this phase the aortic valve is closed (16).…”
Section: Introductionmentioning
confidence: 99%